Characterization Of Natural Resin And Synthetic Resin In Fiber Composite Laminate - Adrian Lim, Zan Kuang (Universiti Sains Malaysia, 2022)
Environment and sustainability issues coupled with increased awareness have urged researchers to focus on natural sources that can substitute synthetic materials. The goal of this study is to characterize the physical and mechanical characteristics of three different materials of natural resin and synthetic resin. This will form the framework for future application for developing natural materials in the manufacturing industry. Natural resin of cashew and neem, and synthetic resin of polyester is characterized by conducting four different tests. Thermogravimetric analysis (TGA), Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray (EDX) analysis and nanoindentation technique are used as physical and mechanical characterization test for the specimens. The results demonstrated that polyester composite has the highest thermal stability as it has stronger functional groups and structural elements whereas cashew and neem have low thermal maturity. The molecular structure of polyester composite is small and compact with low porosity, this resulted in higher hardness between the specimens. Cashew showed higher yield strength and compressive strength due to lower porosity than neem resin. The element compositions of the specimens are similar, this would mean synthetic and natural resin exhibit the same chemical characteristics but impurity in the resins may alter the reactions. The results from nanoindentation showed highest elastic modulus in cashew resin. The delamination of polyester composite layers lead to lower hardness in the mechanical test.